Peristaltic Transport of Non-Newtonian Fluid under Effects of Magnetic Force and Heat Transfer in a Symmetric Channel through a Porous Medium (Baghdad Science Journal, 2024)
In this paper, the effect of magnetic force and nonlinear thermal radiation for peristaltic transport of hybrid bio-nanofluid with the porous medium in a symmetric channel is discussed. The Adomain decomposition technique is utilized for explaining expressions for axial velocity, stream function, temperature, Nusselt number, pressure gradient, magnetic pressure, and magnetic force. The finding shows that gold nanoparticles have an elevation velocity compared with copper nanoparticles, based fluids, and hybrid nanofluids. The magnetic force contours increase when the wave amplitude increases. The temperature and heat transfer rate have been examined clearly. It has been observed that rising thermal radiation increases temperatures. Lastly, the phenomenon of trapping is presented to explain the physical behavior of different parameters. The effects of physical parameters are examined through graphs by using the MATHMATICA software